2016
DOI: 10.1038/ejhg.2016.176
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous splicing mutation in the SF3B4 gene segregates in a family with highly variable Nager syndrome

Abstract: Nager syndrome is a rare preaxial acrofacial dysostosis that is caused by heterozygous loss-of-function variants in SF3B4. This gene encodes for a protein required for the assembly of spliceosomal complexes, being a master gene for splicing regulation. The main clinical features of Nager syndrome include facial-mandibular and preaxial limb malformations, with normal cognitive functioning. Most Nager patients are sporadic, but few familial cases with a highly variable phenotype have been reported. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Direct sequencing of the RT‐PCR amplicon containing exon 13‐27 did not detect any aberrant splicing. Since mutant mRNA may undergo NMRD, we also employed a minigene assay (Figure c) to exclude an effect on transcript maturation using a β‐globin hybrid construct as previously reported (Cassina et al, ). As showed in Figure d, cells transfected with the mutant minigene construct show the same splicing pattern as those expressing the WT plasmid, suggesting that the nucleotide change does not affect splice site recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Direct sequencing of the RT‐PCR amplicon containing exon 13‐27 did not detect any aberrant splicing. Since mutant mRNA may undergo NMRD, we also employed a minigene assay (Figure c) to exclude an effect on transcript maturation using a β‐globin hybrid construct as previously reported (Cassina et al, ). As showed in Figure d, cells transfected with the mutant minigene construct show the same splicing pattern as those expressing the WT plasmid, suggesting that the nucleotide change does not affect splice site recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Splicing events are generated through the synergetic actions of multi-subunit complexes. Although SF3B4 mutations frequently result in the Nager syndrome [7,8], the biological roles of SF3B4 in human cancer are only just beginning to be perceived. Prior studies have shown that SF3B4 expression is upregulated in HCC [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For the remaining 14 non-canonical variants (including exonic changes or those involving intronic residues outside the conserved dinucleotides at the splice site boundaries), concordant results were obtained for 12 substitutions, whereas in two cases (c.7250_7252delACT and c.278G > A) different programs yielded conflicting results. Therefore, we decided to examine all these variants using a classical splicing minigene assay, which we previously successfully employed to analyze ASL , CFTR , and SF3B4 variants [ 37 , 38 , 39 , 40 ] and that has been already used by other groups for validating NF1 changes [ 8 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…PCR fragments including the exon adjacent to each NF1 variant and at least 100 bp of the upstream and downstream introns were amplified from patients’ genomic DNA and cloned into the beta -globin vector, as previously described [ 40 ]. In presence of short introns, a bigger portion of sequence including two adjacent exons was amplified and cloned in the minigene construct.…”
Section: Methodsmentioning
confidence: 99%